(untitled) (Research, Society and Development, 2022)
The main objective of this study is to analyze the production costs of asphalt paving in the municipalities of Feijó and Rio Branco, located in the State of Acre, considering the effects that the distance from suppliers generates on the final price of the product. Taking into consideration that highways are of fundamental importance for both interstate and even international connection, as well as for the transport of cargo and people, it is understood that asphalt paving is also of paramount importance for the promotion of the economy in the various states and municipalities. In the case of the State of Acre, with its geographical location far from major centers, as well as from the main suppliers of asphalt inputs, the evaluation of the production costs of these services can be affected by the existing logistical specificities and the effects caused by the Amazon winter. In this way, it was concluded that the distance from suppliers of asphalt inputs is the main responsible for the high financial costs verified in the paving service in the cities of Feijó and Rio Branco.